A Systematic Review and Meta-Analysis of the Functional MRI Investigation of Motor Neuron Disease - Shen, Dongchao; Cui, Liying; Cui, Bo; Fang, Jia; Li, Dawei; Ma, Junfang (Frontiers in Neurology, 2015)
Background: To assess the use of functional magnetic resonance imaging (fMRI) in motor neuron disease (MND), a systematic review and voxelwise meta-analysis of studies comparing brain activity in patients with MND and in healthy controls (HCs) was conducted to identify common findings across studies. Methods: A search for related papers published in English and Chinese was performed in Ovid Medline, Pubmed and Embase database. Voxelwise meta-analysis was performed using signed differential mapping. Results: The findings from 55 fMRI studies on MND were tabulated, and some common findings were discussed in further details. Conclusions: These ﬁndings are preliminary, sometimes even contradictory, and do not allow a complete understanding of the functional alterations in MND. However, we documented reliable findings that MND is not confined to the motor system, but is a multisystem disorder involving extra-motor cortex areas, causing cognitive dysfunction and deficits in socioemotional and sensory processing pathways.